Analysis Effect of Accrual Discretion Against SILPA (SIKPA) Budget Calculations on Local Government - Abdul Rohman; Rochmawati Daud; Ermadiani Ermadiani (Faculty of Economics, Universitas Sriwijaya, 2018)
The research we carry out is aimed at researching the implementation of measures taken by the local government (discretionary accruals) to the substantial amount of the budget obtained local governments in the current year. This study uses some model approach. The data obtained from reports generated include the Local Government Budget Realization Report (LRA), Statements of Operations (LO) and the Balance Sheet and Statement of Cash Flows (LAK) of each local government who are in the neighborhood of South Sumatera. All Model can show accrual discreation value. But first group (Healy, De angelo, and Hribar) show some variation result numbers with negatif and positive slope. Meanwhile on the second group (Jones and modified) the result shows consisten value and slope. The study results show that in the local government finances there are accruals values of accruals discreation. In addition, existing accrual discretion affects SILPA (SIKPA) of current year budget calculations.